Self-Assembly of a [1 + 1] Ionic Hexagonal Macrocycle and Its Antiproliferative Activity - Singh, Khushwant; Gangrade, Ankit; Bhowmick, Sourav; Jana, Achintya; Mandal, Biman B.; Das, Neeladri (Frontiers in Chemistry, 2018)
A unique irregular hexagon was self-assembled using an organic donor clip (bearing terminal pyridyl units) and a complementary organometallic acceptor clip. The resulting metallamacrocycle was characterized by multinuclear NMR, mass spectrometry, and elemental analyses. Molecular modeling confirmed hexagonal shaped cavity for this metallamacrocycle which is a unique example of a discrete hexagonal framework self-assembled from only two building blocks. Cytotoxicity of the Pt-based acceptor tecton and the self-assembled PtII-based macrocycle was evaluated using three cancer cell lines and results were compared with cisplatin. Results confirmed a positive effect of the metallamacrocycle formation on cell growth inhibition.